Analisis Kebutuhan Belajar Pasien Penyakit Jantung Koroner Berdasarkan Persepsi Pasien dan Perawat di RSUD Raden Mattaher Provinsi Jambi - Yusnilawati; Oktarina, Yosi; Aryani, Tuti; Hayani, Lizda (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Patients with coronary heart disease (CHD) are at risk of experiencing recurrences or recurring attacks. One ofthe actions that nurses can take to prevent recurring attacks is health education. Assessment of the patient'slearning needs is an essential stage in the health education process. The purpose of this study was to determinethe learning needs of CHD patients based on the perceptions of patients and nurses. This research is aquantitative descriptive. The sampling technique used consecutive sampling. The number of respondents was71 people, consisting of 55 CHD patients and 16 heart nurses. Data analysis in the form of mean andpercentage. The mann whitney test was used to see the difference in perception of learning needs of CHDpatients and nurses. Collecting data using the Cardiac Patients Learning Needs Inventory (CPLNI)questionnaire. The highest learning need for CHD patients was based on the patient's perception is the learningneed for miscellaneous aspects with a mean value of 3.91 ± 0.61. Meanwhile, based on the nurse's perception isthe learning need for drug information with a mean value of 4.46 ± 0.42.